Intelligent Giving - Caulkins, Jonathan P.; Cole, Jay; Hardoby, Melissa; Keyser, Donna J. (RAND Corporation, 2023)
Provides an intellectual framework for guiding prospective major donors in giving more effectively to higher education.Although most major gifts are profoundly motivated by charitable intentions, the noble impulse to give to higher education can quickly generate complicated choices. Which school? Which program? Under what terms or conditions? Even very talented people who have enjoyed exceptionally successful careers in business and other fields can become disoriented by academe_s idiosyncrasies. This book provides an intellectual framework for guiding prospective major donors in giving more effectively to higher education. It supplies some insight into the higher education sector, donor opportunities, the development process, and how to think about and get the most from a _negotiation_ with the institution of the donor_s choice. The insights and strategies are culled by a RAND research team mainly from interviews with development officers, institutional leaders, and donors themselves. Ultimately the giving process that works best for any donor will depend on his or her individual interests and needs. The best advice is to be clear on what effect the donor wants his or her gift to have, to seek as much information on the school/situation as possible, and to consult with an attorney and a good financial advisor at all stages of the giving process.